2014
DOI: 10.1097/inf.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immune Responses to Inactivated Influenza A(H1N1)pdm09 Vaccine in Children

Abstract: Background As the influenza AH1N1 pandemic emerged in 2009, children were found to experience high morbidity and mortality and were prioritized for vaccination. This multicenter, randomized, double-blind, age-stratified trial assessed the safety and immunogenicity of inactivated influenza A(H1N1)pdm09 vaccine in healthy children aged 6 months to 17 years. Methods Children received two doses of approximately 15 μg or 30 μg hemagglutin antigen 21 days apart. Reactogenicity was assessed for 8 days after each do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…However, maternal antibodies wane rapidly after birth. Between 6 and 25 months of life, trivalent influenza vaccines (TIV) have limited immunogenicity and protective efficacy ( 2 , 3 ), which may be enhanced in part by MF59 ® adjuvantation ( 4 ). In contrast, influenza vaccines for infants younger than 6 months are lacking: TIV showed poor efficacy ( 3 ) and the live attenuated intranasal vaccine appeared too reactogenic in this age group ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, maternal antibodies wane rapidly after birth. Between 6 and 25 months of life, trivalent influenza vaccines (TIV) have limited immunogenicity and protective efficacy ( 2 , 3 ), which may be enhanced in part by MF59 ® adjuvantation ( 4 ). In contrast, influenza vaccines for infants younger than 6 months are lacking: TIV showed poor efficacy ( 3 ) and the live attenuated intranasal vaccine appeared too reactogenic in this age group ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to another study in which HIV-infected children had a high seroprotection rate of 75% after inoculation with the inactivated split-virion AS03-adjuvanted pandemic H1N1(2009) vaccine, 14 while another previous study showed that the seroprotection rates of the inactivated influenza A (H1N1) pdm 2009 vaccine in healthy children were 78 to 98% at 21 days. 27 A previous study in response to TIV reported that 73% of healthy children exhibited protective responses. 28 In contrast, a similar previous study showed the proportion of seroconversion for H1N1, H3N2 and influenza B strains in HIV-infected children were 47.5, 50.0 and 40.0%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier attempts at vaccinating against influenza in these age groups have been quite discouraging and associated with significant adverse reactions. [71][72][73][74] However, these studies did not explore the potential of mucosal vaccination, but other vaccine studies have evaluated the use of oral priming in neonatal Macaque and Pig models against Simian immunodeficiency virus and rotavirus, albeit using live attenuated vaccines, with promising results. 75,76 As oral priming is more effective for stimulating immune protection against enteric infections we also intend to test neonatal vaccination against rotavirus infections, using a CTA1-VP6-DD fusion protein.…”
Section: Discussionmentioning
confidence: 99%